ANALISIS PROBLEMATIKA PEMBELAJARAN MATEMATIKA DI SEKOLAH MENENGAH PERTAMA DAN SOLUSI ALTERNATIFNYA - Raras Kartika Sari (Universitas Insan Budi Utomo, 2019)
The study was conducted aimed at finding out the problems in learning mathematics in junior high schools, especially at SMP Muhammadiyah 8 Batu with alternative solutions. The method used in this study is a qualitative research approach. The research subjects were two students from class IX-1 and IX-6 each representing students from homogeneous and heterogeneous classes, as well as two math teachers at SMP Muhammadiyah 8 Batu who each taught in homogeneous and heterogeneous classes . Analysis of the data used in this study is analysis of observations, questionnaire results and interview transcripts. Based on the results of the research, it was found that the problem of mathematics learning in SMP Muhammadiyah 8 Batu is 1) poor mathematical mastery; 2) learning motivation that is not good; 3) the use of instructional media and 4) the application of learning methods. An alternative solution to these problems is the need for scaffolding when students experience difficulties, there is a personal approach to students, it is necessary to use more interesting learning media, for example macromedia flash and educational games, the application of learning methods tailored to the characteristics of good students for homogeneous and heterogeneous classes.